A pinch of culinary science : boiling an egg inside out and other kitchen tales - Hopia, Anu Inkeri; Fooladi, Erik Cyrus (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Various food and cooking myths, with a culinary explanation, and including in-chapter recipes.
The real thing? : the chemistry and psychology of an apple pie -- Boiling an egg from the inside out -- In the beginning there was an egg -- Mussels on acid -- Sausage engineering -- Mustard, fiercely yours -- The potatoes that refused to become tender -- Gravlax and a pinch of salt chemistry -- The art of heating -- Cold skillet : juicy fish -- Tempering the meat before cooking, ...or maybe not -- Cooking pits : prehistoric cooking meets science -- White wine in cooking should always be dry, right? -- Taking stock of broth -- Salt shapes the pasta -- You can see it, hear it, taste it and feel it : what is it? it is the taste of food! -- Can you cut down on the salt without affecting the taste? -- Physics takes the cake -- The great norwegian porridge feud -- The inevitable dishes -- Glossary.
OCLC-licensed vendor bibliographic record.
Keywords: Cooking -- Popular works; Food habits -- Popular works; SOCIAL SCIENCE / Agriculture & Food; TECHNOLOGY / Food Science